Evaluation of Maize Genotypes against Southern Leaf Blight (Bipolaris Maydis) During Summer Seasons at Rampur, Chitwan - Rijal, Tirtha Raj; Koirala, Keshab Babu; Karki, Mina (International Journal of Applied Sciences and Biotechnology, 2017)
Maize genotypes were screened at research field of National Maize Research Program, Rampur, Chitwan on 20 maize genotypes during 2015 and 2016 summer season with the objective of identification of resistant genotypes against southern leaf blight caused by Bipolaris maydis. Field experiment was laid out in randomized complete block design with three replications. Disease scoring was done as percentage of leaf area infected using 1-5 rating scale. In both the years among the tested genotypes, disease severity and grain yield varies significantly. None of the genotypes reacted for resistant whereas four genotypes; 05SADVI, BGBYPOP, RAMS03F08 and RML-32/RML-17 were moderately resistant over the years. For grain yield most of the tested genotypes produced comparatively lower grain yield however RML-32/RML-17 was superior for grain yield (3.1 t/ha) over the years. Int. J. Appl. Sci. Biotechnol. Vol 5(4): 532-536